An Ordinance to Prohibit the Carrying of Concealed Weapons Within the Corporate Limits of the Town of Allendale, §§ 1-3, EDGEFIELD ADVERTISER, May 13, 1880, at 4 (Allendale, South Carolina). - (:unkn) unknown (My University, 1880)
That on and after the passage of this ordinance the carrying concealed about the person of any pistol, dirk, butcher-knife, sword or spear-cane, metal knuckles or other weapons of offence is hereby prohibited within the corporate limits of the town of Allendale, under a penalty of not less than ten dollars fine or ten days' imprisonment for each and every offence, upon conviction thereof;Provided,that this ordinance shall not apply to the sheriffs of this State or their deputies, or to any special or regular constable, or to the town marshal or his duly appointed assistants, in the discharge of their respective duties as such.
Keywords: CARRY - CONCEALED